2016
DOI: 10.1021/acs.jafc.6b03424
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Apple Procyanidins Ameliorates Insulin Resistance via Suppression of Pro-Inflammatory Cytokine Expression in Liver of Diabetic ob/ob Mice

Abstract: Procyanidins, the main ingredient of apple polyphenols, are known to possess antioxidative and anti-inflammatory effects associated closely with the pathophysiology of insulin resistance and type 2 diabetes. We investigated the effects of orally administered apple procyanidins (APCs) on glucose metabolism using diabetic ob/ob mice. We found no difference in body weight or body composition between mice treated with APCs and untreated mice. A 4 week oral administration of APCs containing water [0.5% (w/v)] ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…However, weight loss can restore the unbalanced GM ( Liu et al, 2017 ). Numerous animal studies demonstrate that PPs can treat obesity and improve the resultant metabolic syndromes in HFD-induced and (ob/ob) obese mice, including hyperglycemia, insulin resistance (IR), and inflammation, as well as restore the GM balance ( Axling et al, 2012 ; Roopchand et al, 2015 ; Ogura et al, 2016 ). However, crowd tests showed inconsistent results: many studies employing fruit juices/extracts (which contain abundant PPs) found that they can alleviate hyperglycemia and IR in people suffering from T2DM, ( Chiva-Blanch et al, 2012 ; Saez-Lopez et al, 2017 ) while other studies found no significant effect ( Botden et al, 2012 ; Woerdeman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, weight loss can restore the unbalanced GM ( Liu et al, 2017 ). Numerous animal studies demonstrate that PPs can treat obesity and improve the resultant metabolic syndromes in HFD-induced and (ob/ob) obese mice, including hyperglycemia, insulin resistance (IR), and inflammation, as well as restore the GM balance ( Axling et al, 2012 ; Roopchand et al, 2015 ; Ogura et al, 2016 ). However, crowd tests showed inconsistent results: many studies employing fruit juices/extracts (which contain abundant PPs) found that they can alleviate hyperglycemia and IR in people suffering from T2DM, ( Chiva-Blanch et al, 2012 ; Saez-Lopez et al, 2017 ) while other studies found no significant effect ( Botden et al, 2012 ; Woerdeman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…which PACs regulate metabolic health, ranging from immunomodulatory signaling, stimulation of glucose and lipid metabolism, dampening of metabolic endotoxemia, as well as through inhibition of digestives enzymes [7][8][9] . However, since high molecular weight PACs are poorly absorbed in the small intestine 10 , they reach the large intestine where they interact with the gut microbiota and exert prebiotic-like effects 11 .…”
mentioning
confidence: 99%
“…Vitamin C (ascorbic acid) is well known for its effects on the immune system, and in states of increased inflammation, vitamin C levels tend to decrease in the body [52]. Several studies in cell, animals, and humans have suggested that red-colored foods and/or their isolated constituents [53] may assist with reducing systemic inflammation and bolstering immune status by reducing infections, including watermelon [54], apples [55][56][57][58][59][60][61], cherries [61][62][63], cranberries [57,64,65] pomegranate [66][67][68][69][70], and raspberries [71][72][73].…”
Section: Red Foods and Inflammationmentioning
confidence: 99%